A comparison of haemodynamics between subcranial-intracranial bypass and the traditional extracranial-intracranial bypass. (2nd November 2017) - Yu, Zaitao; Yang, Yang; Shi, Xiang'en; Qian, Hai; Liu, Fangjun
Abstract: Background: Ischemic cerebrovascular diseases are traditionally treated using an extracranial-intracranial (EC-IC) bypass. The use of the internal maxillary artery (IMA) in the subcranial-intracranial (SC-IC) bypass was recently described as an alternative treatment. However, the haemodynamics of this new approach have not been defined. Methods: The haemodynamic parameters (flow volume [FV], internal diameter [ID], time-averaged mean velocity [TAM], pulsatility index [PI] and resistance index [RI]) of the IMA-radial artery graft (RAG)-middle cerebral artery (MCA) ( n  = 12) bypass and superficial temporal artery (STA)-MCA bypass ( n  = 18) were measured using intraoperative duplex ultrasonography and compared. Results: The FV was 81.36 ± 30.41 (62.05–100.70) ml/min for the IMA-RAG-MCA bypass. This was significantly higher than that of the STA-MCA bypass (27.25 ± 9.32 (22.62–31.88) ml/min; P  < .01). The ID and TAM in the IMA-RAG-MCA bypass were higher than in the STA-MCA bypass ( P  < .01; P  < .01). No significant differences were observed in PI ( P  ≈ .21) and RI ( P  ≈ .08). The early patency rate (one month after the operation) was 100% for the IMA-RAG-MCA bypass and 94% for the STA-MCA bypass. Conclusions: The IMA-RAG-MCA bypass provides moderate to high blood flow to the revascularized territory and blood flow was higher by this method than the STA-MCA bypass.